Memoirs of the Mexican Revolution : including a narrative of the expedition of General Xavier Mina. To which are annexed some observations on the practicability of opening a commerce between the Pacific and Atlantic oceans, through the Mexican isthmus, in the province of Oaxaca, and at the Lake of Nicaragua; and the vast importance of such commerce to the civilized world. - Robinson, William Davis (2015)
UANL